Control of Physical and Biochemical Parameters Influencing Exogeneous Cargo Protein Association to Extracellular Vesicles Using Lipid Anchors Enables High Loading and Effective Intracellular Delivery - Antonin Marquant; Jade Berthelot; Claudia Bich; Zeineb Ibn Elfekih; Laurianne Simon; Baptiste Robin; Joël Chopineau; David Tianpei Wang; Samuel Jay Emerson; Aijun Wang; Clément Benedetti; Simon Langlois; et al. (Journal of Extracellular Biology)
ABSTRACT Despite biomolecule delivery is a natural function of extracellular vesicles (EVs), low loading of exogenous macromolecules such as proteins into EVs limits their interest as convincing protein delivery systems for health applications. In this context, lipid‐anchorage of exogenous cargo into EV membrane recently emerged as a promising option to enable their vectorisation into cells. Nevertheless, this option was not explored for protein intracellular delivery, and further characterisation of critical parameters governing the association of a lipid‐anchored cargo protein to EVs is still needed to confirm the relevance of this anchorage strategy. Therefore, we sought to identify these parameters in a precise and quantitative manner, using bulk and single nanoparticle analysis methods to identify protein loading capacity and subsequent intracellular delivery. We identified incubation temperature, cargo concentration, lipid anchor (LA) structure (lipid nature, linker) and EV origin as critical factors influencing maximal EV loading capacity. Precise control of these parameters enabled to load cargo protein close to EV saturation without hindering cellular delivery. The structural properties of LA influenced not only cargo protein/EV association but also intracellular delivery into different carcinoma cell lines. By thoroughly characterising Lipid‐PEG‐protein anchorage, this study evidences the interest of this tunable and controllable approach for efficient EV protein delivery.